The effect of a repeated intensive programme in patients with mid-stage Huntingtonʼs disease - Dagmar Pavlů; Irena Opatrná-Novotná; Jan Smyčka; David Pánek (Karolinum Press, 2021)
The purpose of the study was to evaluate the effect of a repeated 1-week intensive programme in patients with mid-stage Huntington's disease on stability and quality of life. 12 patients completed two 1-week programmes, separated by a one-year interval. Each programme consisted of a 120-minute intervention in the form of a fitness exercise, procedures targeting static and dynamic postural stability, procedures of respiratory physiotherapy and orofacial region therapy. The patient completed a total of 4 evaluations using the Sit to Stand Test, Timed up and Go Test and completed the quality of life SF-36 questionnaire. Statistically significant changes have been shown in the Sit-and-stand test in both years. Weaker but still significant changes were found in the TUG test only in the first year, while there was improvement in the second intervention year that was not statistically significant. Evaluation of the quality of life suggested a positive influence of physical activity in the dimensions: restriction caused by emotional problems, somatic pain and change of health. Our results suggest that a repeated, intensive one-week intervention can have a positive influence on postural stability and can contribute to the improvement of some quality of life dimensions in patients with mid-stage HD.